Serving God in today's cities : facing the challenge of urbanization - Johnstone, Patrick (Colorado Springs, CO : GMI, 2015)
For the first time ever, more people now live in cities than outside them. Join veteran researcher and missiologist Patrick Johnstone as he explores the fastest growing cities and megacities, showing how Christian workers address people's spiritual, physical, and social needs. Cities offer big headaches and vast opportunities, and agencies that once focused on rural work are increasingly turning their attention to urban centers. Journey with Patrick as he shares God's heart for the city and introduces pastors, missionaries, and community workers who are addressing urbanization's key challenges. God has a heart for today's cities. See how you can join this urgent mission.--Back cover.
Part 1: Eyes to see. The first urban century -- Cities: headache or opportunity? -- What God thinks of cities -- Part 2: Eight critical responses. Action 1: Pray together -- Action 2: Exegete the city -- Action 3: Push against urban poverty -- Action 4: Reach out to diasporas -- Action 5: Form healthy churches -- Action 6: Confront sinful structures -- Action 7: Address real human pain directly -- Action 8: Embrace a wider vision -- Conclusion: Greater things are still to come.
Includes bibliographical references.
Keywords: Church and the world; Christianity; Missions; Evangelicalism; Mission of the church; Urbanization; Metropolitan areas; City missions; Christianity; Urbanization; City missions; Metropolitan areas